Climate Stabilisation Under Net Zero CO2 Emissions - Alexander Borowiak; Andrew D. King; Josephine R. Brown; Chris D. Jones; Michael Grose (Earth's Future)
Abstract Under the Paris Agreement, signatories aim to limit the global mean temperature increase to well below 2°C above pre‐industrial levels. To achieve this, many countries have made net zero greenhouse gas emissions targets, with the aim of halting global warming and stabilizing the climate. Here, we analyze the stability of global and local temperatures in an ensemble of simulations from the zero‐emissions commitment Model Intercomparison Project, where CO2 emissions are abruptly ceased. Our findings show that at both the global and local level stabilization does not occur immediately after net zero CO2 emissions. The multi‐model median (mean) global average temperature stabilizes after approximately 90 (124) years, with an inter‐model range of 64–330 years. However, for some models, this may underestimate the actual time to become stable, as this is the end of the simulation. Seven models exhibited cooling post‐emission cessation, with two of the models then warming after the initial cooling. One model gradually warmed through the entire simulation, while another had alternating cooling and warming. At the local level, responses varied significantly, with many models simulating the reversal of trends in some areas. Changes at the local level, at many locations, continue beyond the stabilization of global temperature and are not stable by the end of the simulations.